Evaluation of hematological parameters as an indicator of disease severity in Covid‐19 patients: Pakistan's experience. Issue 6 (24th May 2021) - Waris, Abdul; Din, Misbahud; Khalid, Atiqa; Abbas Lail, Raees; Shaheen, Asmat; Khan, Nida; Nawaz, Mehboob; Baset, Abdul; Ahmad, Imtiaz; Ali, Muhammad
Abstract: Background: The severity of COVID‐19 could be evaluated by examining several blood parameters mainly white blood cell (WBC) count, granulocytes, platelet, and novel hemocytometric markers neutrophils to lymphocyte ratio (NLR), platelet‐to‐lymphocyte (PLR), and lymphocyte to monocyte ratio (LMR). The current study was conducted to investigate alteration in blood parameters and their association with the severity and mortality of COVID‐19 patients. Methodology: An observational cross‐sectional study was conducted retrospectively, a total of 101 COVID‐19 positive patients were examined: 52 were mild, 24 were moderate, 09 were severe, and 16 were critically diseased patients. We also recorded 16 deaths associated with the critical group. The overall mean age observed in our study was 48.94 years, where the mean age for critical individuals was 62.12 ± 14.35 years. Results: A significant association between the disease severity and elevation in blood parameters were observed. The WBC's and granulocyte count were significantly increased ( p value <0.001) while the mean platelet count (165.0 × 10 9 /L) and red blood cell volume distribution width (RDW) were decreased in the critical group (57.86%) compared to mild group's patients (177.3%) ( p  = 0.83). The lymphocytes count was decreased in critical patients (1.40 × 10 9 /L) compared to mild patients (1.92 × 10 9 /L) ( p  = 0.28). A significant association was observed in platelet‐lymphocyte ratio ( p  < 0.001), Neutrophil‐Lymphocyte ratio ( p  = <0.001), and Lymphocyte‐Monocyte ratio (0.011). Conclusion: These blood parameters could be used as a suitable biomarker for the prognosis and severity of COVID‐19. Evaluating novel hemograms NLR, PLR, and LMR can aid clinicians to identify potentially severe cases at early stages, initiate effective management in time, and conduct early triage which may reduce the overall mortality of COVID‐19 patients. Abstract : Hematological findings as indicator of disease severity in Covid‐19 patients.